Changes in Corticospinal Circuits During Premovement Facilitation in Physiological Conditions - Cirillo, Giovanni; Di Vico, Ilaria Antonella; Emadi Andani, Mehran; Morgante, Francesca; Sepe, Giovanna; Tessitore, Alessandro; Bologna, Matteo; Tinazzi, Michele (Frontiers in Human Neuroscience, 2021)
Changes in corticospinal excitability have been well documented in the preparatory period before movement, however their mechanisms and physiological role have not been entirely elucidated. We aimed to investigate the functional changes of excitatory corticospinal circuits during a reaction time (RT) motor task (thumb abduction) in healthy subjects (HS). 26 HS received single pulse transcranial magnetic stimulation (TMS) over the primary motor cortex (M1). After a visual go signal, we calculated RT and delivered TMS at three intervals (50, 100, 150 ms) within RT and before movement onset, recording motor evoked potentials (MEP) from the abductor pollicis brevis (APB) and the task-irrelevant abductor digiti minimi (ADM). We found that TMS increased MEP APB amplitude when delivered at 150, 100 and 50 ms before movement onset, demonstrating the occurrence of premovement facilitation (PMF). MEP increase was greater at the shorter interval (MEP 50) and restricted to APB (no significant effects were detected recording from ADM). We also reported time-dependent changes of the RT and a TMS side-dependent effect on MEP amplitude (greater on the dominant side). In conclusion, we here report changes of RT and side-dependent, selective and facilitatory effects on the MEP APB amplitude when TMS is delivered before movement onset (PMF), supporting the role of excitatory corticospinal mechanisms at the basis of the selective PMF of the target muscle during the RT protocol.